Caracterização física do uso e ocupação da bacia hidrográfica do Rio Cascavel - Tosin, Gladis Aparecida Sandi (2005)
This work had as objective to characterize the use forms and occupation of Cascavel River basin, looking for to bring a diagnosis of the use and urban occupation in the basin, being used techniques of remote sensoriamento and geographical information system, with the use of satellite image TM/Landsat of the year of 2002, official registers about the occupation of the same, trying to establish a prognostic of the current environmental condition of the basin. They were diagnosed the system of garbage collection, varrição system, sewerage system system, system of gallery of pluvial water, existent paving in the urban area and the evolution of the divisions into lots in the urban area. In the rural area, the use of the soil was diagnosed, identifying the vegetation, culture and nude soil. The analyses of the results showed that the basin presents risks geoambientais and that the tendency of occupation of the soil and the demographic growth, they generated areas potentially problems once the disordered occupation of the physical middle caused the degradation of the natural resources of the soil, of the vegetation and they contributed considerably for to deterioration of the resources hidrics.